An instrument to measure medical students’ perceptions of the assessment environment: Development and initial validatioN - Sim, J.H.; Wen, T.T.; Hong, W.H.; Jamuna, V.; Hamimah, H. (2016)
This study aimed to develop an instrument for measuring students’ perceptions of the assessment environment in undergraduate medical programme and to examine the instrument’s psychometric properties.